Professor Karol Latowski – plant taxonomist, carpologist and geobotanist - Jackowiak, Bogdan; Żukowski, Waldemar (Biodiversity: Research and Conservation, 2015)
Professor Karol Latowski – plant taxonomist, carpologist and geobotanist